حديث قطع المرأة والكلب والحمار للصلاة دراسة تطبيقية في ضوء علم مختلف الحديث - Rohaizan, Baru; Abdallah Daoud Ibrahim, Theeb (2020)
The science of "different hadiths" is one of the most important sciences for jurists and hadith scholars, the problem of research: there is a conflict between the hadiths that say that the passage of women, donkeys, and dogs, invalidates prayer, and with hadiths that say the contrary, is there a real conflict between these hadiths? How did the scholars direct these conversations? The research answers questions, discusses the words of scholars, explains hadiths, and gives the most correct opinion. The aim of the research is to show the role of scholars in guiding seemingly conflicting conversations, how scientists coordinated them, and to demonstrate the great effort made by the scholars of this nation in defending the Sunnah. The researcher took the inductive approach: in the selection of hadiths and the focus was on the six famous books in hadith, because of their importance for preserving the origins of the Sunnah, and the analytical and critical approach was the course of the researcher in the study of the words of scholars and the hadith and made the researcher arrange the words of the scholars in pushing the conflict on the approach of the modernists, he began to combine and then copy the weighting and then the statement of opinion of the most merciful, God willing. The results of this research are summarized: scientists have three paths to pushing the conflict: plural, cancellation and weighting. The researcher found that the most likely view of the public was because of the realization of the evidence and not to neglect it.